AI-Powered Data Cleansing for Healthcare: Improving Data Quality in Patient Records and Claims Processing - Dharmeesh Kondaveeti; Prabhu Krishnaswamy; Subhan Baba Mohammed (Journal of Science & Technology, 2023)
The advent of artificial intelligence (AI) and machine learning (ML) has brought significant advancements across various sectors, with healthcare being one of the most promising domains for AI-driven transformation. This research paper explores the potential of AI-powered data cleansing methods in the healthcare sector, specifically targeting the enhancement of data quality in patient records and claims processing. Healthcare systems are notoriously inundated with large volumes of data, often characterized by inconsistencies, inaccuracies, and incomplete entries that undermine the efficiency of healthcare operations. The critical need for high-quality data is underscored by the industry's reliance on accurate patient records for diagnosis, treatment planning, and insurance claims processing. However, the complexity of healthcare data, which stems from its multi-source and heterogeneous nature, poses significant challenges for traditional data cleansing methods. Consequently, AI and ML techniques have emerged as powerful tools to address these challenges, offering unprecedented capabilities for automating the detection and correction of errors in healthcare data.This paper delves into the architecture, algorithms, and models that form the backbone of AI-powered data cleansing systems. The focus will be on supervised and unsupervised learning techniques, natural language processing (NLP), and probabilistic models that are applied to standardize, verify, and correct anomalies in patient records and insurance claims. For patient records, the research discusses methods for handling missing data, identifying duplicate entries, resolving conflicting information, and ensuring the proper structuring of medical histories across different healthcare providers. In the domain of claims processing, the discussion covers AI techniques that enhance the accuracy of claim submissions, reduce rework caused by erroneous entries, and ensure compliance with insurance standards and regulatory requirements. Additionally, the use of AI in recognizing patterns that indicate fraud or abuse in claims processing will be considered, showcasing how these systems improve the overall integrity of healthcare data.The paper also addresses the challenges associated with implementing AI-driven data cleansing systems in real-world healthcare settings. These challenges include the heterogeneity of data formats across different electronic health records (EHR) systems, the need for interoperability between various healthcare databases, and the privacy and security concerns inherent to handling sensitive patient information. While AI offers significant promise in overcoming these issues, the integration of such systems into existing healthcare infrastructures requires careful planning, including robust model validation, continuous monitoring, and adherence to ethical and legal standards governing patient data.Case studies and empirical evaluations of existing AI-powered data cleansing systems are presented to highlight the practical applications and the outcomes achieved in terms of improved data quality and operational efficiency. The studies demonstrate how AI technologies have been used to detect and correct inconsistencies in patient data, streamline the claims submission process, and improve overall healthcare delivery. Performance metrics such as accuracy, precision, recall, and F1 scores are employed to assess the effectiveness of these systems in real-world scenarios. Moreover, the impact of AI on reducing manual intervention, lowering administrative costs, and speeding up the reimbursement process is critically analyzed, providing a comprehensive understanding of the economic and operational benefits derived from AI-driven data cleansing solutions.Furthermore, the paper discusses future directions for research in this area, including the potential of deep learning models, federated learning, and other advanced AI techniques to further improve data cleansing processes. The role of explainable AI (XAI) is also examined, as it is crucial to build trust and ensure transparency in the decision-making processes of AI systems, especially in sensitive domains like healthcare. The scalability of AI-powered data cleansing solutions, especially in large healthcare networks and across different jurisdictions with varying regulatory landscapes, is explored in detail.
Keywords: AI-powered data cleansing; machine learning